The Effect of Doxycycline on PMA-Induced MUC5B Expression via MMP-9 and p38 in NCI-H292 Cells - Chang Hoon Bae; Seung Min Chen; Heung-Man Lee; Si-Youn Song; Yong-Dae Kim (Clinical and Experimental Otorhinolaryngology, 2011)
ObjectivesDoxycycline is commonly used in medicine for its bacteriostatic antimicrobial properties. Recent studies have reported that doxycycline also has anti-inflammatory effects. Matrix metalloproteinase (MMP)-9 has been found to be involved in the physiological and pathological process of inflammatory airway disease. Phorbol 12-myristate 13-acetate (PMA), a protein kinase C activator, is known to stimulate the expression of MMP and mucin genes in the airway and intestinal epithelial cells. Therefore, the effects and signal pathways of doxycycline on PMA-induced MUC5B expression dependent MMP-9 in human airway epithelial cells were investigated.MethodsIn human NCI-H292 airway epithelial cells, MUC5B and MMP-9 mRNA expression, MUC5B protein expression, and MMP-9 protein activity after the treatment with PMA, MMP-9 or doxycycline were determined by reverse transcriptase-polymerase chain reaction, enzyme immunoassay, gelatin zymography, and Western blot analysis.ResultsPMA increased MMP-9 and MUC5B expression. MMP-9 increased MUC5B expression. Doxycycline inhibited PMA-induced MUC5B expression, and PMA-induced MMP-9 mRNA expression and protein activity. Doxycycline inhibited phosphorylation of p38 induced by PMA and MMP-9.ConclusionThe results of this study suggest that doxycycline inhibited PMA-induced MUC5B mRNA expression and protein production through the MMP-9 and p38 pathways in human NCI-H292 airway epithelial cells.